(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The article discusses the changes in the structural composition of the black soils of Lori plain, which occurs as a result of uncoordinated human economic activities. The results of our field studies show that the structural elements in uncultivated black soils are stable and the soils have a well-defined structure. Compared to non-cultivated soils, the amount of water-resistant aggregates in the topsoil of cultivated soils is quite low, and the topsoil is significantly dusty.